Effect of Pulmonary Involvement on Bath Indexes, Quality of Life and Psychological Symptoms in Patients with Ankylosing Spondylitis - Hale Karapolat,; Funda Atamaz,; Yeşim Akkoç,; Alev Gürgün,; Recep Savaş,; Yeşim Kirazlı,; Nurullah Akkoç, (Archives of Rheumatology, 2009)
Objective: Pain and stiffness disturb the psychological status and quality of life in ankylosing spondylitis (AS) patients, which may be further deteriorated by pulmonary involvement. Therefore, detection of pulmonary involvement in AS patients is important. In this study, we aimed to detect pulmonary involvement in AS patients and to assess the effects of pulmonary involvement on Bath indexes, quality of life and psychological symptoms. Material and Methods: The study included 26 AS patients (mean age: 47.5±10.8 years). Pulmonary status of the patients was assessed by spirometric measurements and radiographic methods (chest X-ray, high resolution computerized tomography [HRCT]); clinical status was assessed by Bath indexes (Bath Ankylosing Spondylitis Disease Activity Index [BASDAI], Bath Ankylosing Spondylitis Functional Index [BASFI], Bath Spondylitis Metrology Index [BASMI], Bath Ankylosing Spondylitis Radiology Index [BASRI]); quality of life was assessed by Nottingham Health Profile-1 (NHP) and St. George Respiratory Questionnaire (SGRQ); and psychological symptoms were assessed by Beck Depression Scale (BDS). Results: Respiratory function tests were impaired in 15.4% of the patients (n: 3/1, restrictive/obstructive). HRCT revealed pathologic findings in 20.9% of the patients (n: 5). A negative correlation was detected between forced expiratory volume in 1 second (FEV1%) and BASFI (r=-0.56, p<0.01). No significant correlation was observed between the other respiratory function tests and HRCT, duration of disease, Bath indexes (BASDAI, BASFI, BASMI, BASRI), NHP, SGRQ, and BDS (p>0.05). Conclusion: Our study showed that pulmonary involvement may be observed among non-smoker AS patients with longer duration of disease; however, pulmonary involvement is not related with clinical status, quality of life or psychological symptoms. (Turk J Rheumatol 2009; 24: 183-9)